Homology modeling and docking studies of ENPP4: a BCG activated tumoricidal macrophage protein. Issue 1 (December 2016) - Yan, Dongmei; Han, Weiwei; Dong, Zehua; Liu, Qihui; Jin, Zheng; Chu, Dong; Tian, Yuan; Zhang, Jinpei; Song, Dandan; Wang, Dunhuang; Zhu, Xun
Abstract Background The 3D structure and functions of ENPP4, a protein expressed on the surface of Bacillus Calmette–Guerin (BCG)-activated macrophages, are unknown. In this study, we analyzed the 3D structure of ENPP4 and determined its tumoricidal effects on MCA207 cells. Results Homology modeling showed that Arg305, Tyr341, Asn291, and Asn295 are important residues in substrate, adenosine triphosphate (ATP), binding. A molecular dynamics study was also carried out to study the stability of ENPP4 (including zinc atoms) as well as its ligand–enzyme complex. BCG increased ENPP4 expression in macrophages, and specific blocking of ENPP4 in BCG-activated macrophages (BAMs) significantly reduced their cytotoxicity against MCA207 cells. Conclusions These results indicate that zinc remains inside the ENPP4 protein, a BCG activated tumoricidal macrophage protein, throughout the simulation. Important information for the design of new inhibitors was obtained.